Pengaruh Persentase Penambahan Bubuk Serat Oyong (Luffa acutangula) dan Lama Pengadukan terhadap Karakteristik Krim Body Scrub - Ahadianti, Kadek Mei; Wrasiati, Luh Putu; Ganda Putra, Gusti Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
Body scrub cream is a semi-solid dosage form containing one or more dissolved or dispersed medicinal ingredients in suitable base ingredients and serves to smooth the body's skin and remove damaged skin cells with the help of scrub material. Oyong fiber (Luffa acutangula) is used as a scrubber material that is natural, biodegradable and inexpensive. The aim of this study to know the effect of the addition of oyong fiber powder and stirring time to the characteristics of body scrub cream and to determine the percentage of the addition of oyong fiber powder  and length of stirring to produce the best body scrub cream. This research uses factorial randomized block design with two factors. The first factor is the percentage of the addition of the Oyong fiber powder consisting of 3 levels namely 5, 7, 9 and 11% and the second factor is the stirring time consisting of 10, 15, and 20 minutes. Data were analyzed by analysis of variance and continued by Tukey's test. The results of the study showed that the addition loofah (Luffa acutangula) fiber powder addition and the stirring time very affected the pH, viscosity, spreadability power, adhesion power and overall acceptance of the body scrub cream. The interaction between the addition loofah (Luffa acutangula) fiber powder addition and the stirring time very affected the viscosity and the spreadability power.  Addition of 9% of loofah (Luffa acutangula) fiber powder and 20 minutes of the stirring time was the best treatment for body scrub cream with characteristics as follows: pH 4.60, viscosity 37600 cp, homogeny, spreadability power 4.6 cm, adhesion power 9.88 seconds, separation ratio=1 and overall acceptance 5,90 (rather like to like). Keywords : body scrub cream, Luffa acutangula, stirring time